Hubungan Tingkat Pengetahuan, Usia, Jenis Kelamin, dan Kesehatan Mental dengan Perilaku Berisiko Terkena Infeksi Menular Seksual pada Remaja di Wilayah Kerja Puskesmas Menteng Palangka Raya: The Relationship of Knowledge, Age, Gender and Mental Health with Behavior at Risk for Sexually Transmitted Infections in Adolescents in the Work Area of Menteng Palangka Raya Public Health Center - Stefanicia Stefanicia; Ivana Devitasari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Background: In adolescence, many changes of biological, psychological, and social, with the persistence of incident cases of sexually transmitted infections, become evidence that teenagers are prone to risky behavior sexually transmitted infections. Objective: This study aims to determine the level of knowledge, age, gender, and mental health with behavior at risk of sexually transmitted infections in adolescents in the work area of Menteng Palangka Raya Public Health Center. Method: This was an observational analytic study with a cross-sectional design. The sample size in this research is 74 teenagers in the work area of Menteng Palangka Raya Public Health Center with the method of sampling with simple random sampling. Finding: The result of the bivariate analysis of this study showed that the level of knowledge with risky behavior was affected by STI (p = 0.000), age (p = 0.000), gender (p = 0.607), mental health (p = 0.013). Conclusion: There is a relationship of knowledge, age, and mental health with behaviors at risk of sexually transmitted infections. The result of the multivariate analysis showed the most dominant age with the result of Odd Ratio (OR) or Exp (B) = 8.911. For that purpose, the program organizes, evaluates or re-activates the Counseling Guidance, Health Care for Youth Care (HCYC), targeting teenagers and their parents, and establishing special NGOs or counselors that concentrate on adolescents.